2019
DOI: 10.1088/2058-6272/ab2a3e
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cold atmospheric pressure plasma jet on seed germination and seedlings growth of fenugreek (Trigonella foenum-graecum)

Abstract: The effects of cold atmospheric-pressure plasma jet (CAPPJ) were investigated on germination and early seedling growth of fenugreek (Trigonella foenum-graecum L) seeds. A two-electrode argon CAPPJ system with and without an additional grounded electrode [accelerating grounded (AG) electrode] was used at different exposure times. After 16 h of observation, the germination rates increased by 4 and 7 times, without and with using an AG electrode, respectively, for 1 min of plasma exposure. An increase in shoot fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 50 publications
0
16
0
1
Order By: Relevance
“…In Leucaena leucocephala seeds, this resistance barrier to water penetration was similarly identified as the surface of the seed coat along with the light line and was possible to overcome by plasma treatment [9]. Research on fenugreek seeds has additionally found that exposure to an atmospheric pressure plasma jet has progressively peeled off macrosclereid cells from the surface of the seeds [43,44].…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…In Leucaena leucocephala seeds, this resistance barrier to water penetration was similarly identified as the surface of the seed coat along with the light line and was possible to overcome by plasma treatment [9]. Research on fenugreek seeds has additionally found that exposure to an atmospheric pressure plasma jet has progressively peeled off macrosclereid cells from the surface of the seeds [43,44].…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…It is generally accepted that CAPPs technology can accelerate seed germination and young seedling growth (Bafoil et al 2018; Fadhlalmawla et al 2019). In this study, we found that Arabidopsis seedlings increased in length and fresh weight after being treated with CAPPs for 1 min (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, after longer exposures (20–30 min) saturation and negative effects occur. Fenugreek was studied by Fadhlalmawla et al [ 60 ], where enhancements of the seed germination rate by 7 and 4 times and growth parameters could occur, probably due to the etching of the seed surface stimulated by the plasma streamers and high electric field. Vejrazka et al [ 38 ] confirmed inhibitory effects on fenugreek, when the highest reduction of germination (over 40%) was recorded after 50 s of NTP treatment.…”
Section: Seed Germinationmentioning
confidence: 99%
“…Higher doses had the opposite effect. In Fadhlalmawla et al [ 60 ], the authors showed for fenugreek seeds that plasma treatment affected the growth of seedlings, measured as root and shoot length and fresh and dry weight of root and shoot, but the effect on seedling growth was not consistent. The changes in red clover plant’s internal processes, the beneficial root nodulation and their communication with microorganisms were reported [ 65 , 75 ], where the NTP stress change the amounts of flavonoids important for communication with nitrogen fixing strains of rhizobacteria on the roots of red clover.…”
Section: Seedling Initial Growthmentioning
confidence: 99%
See 1 more Smart Citation